Development of a Coprecepting Model for a Preceptor-in-Training Program for New Practitioners. (August 2019) - McCleary, Emily J.; Thompson Bastin, Melissa L.; Bissell, Brittany D.; Cook, Aaron M.; Pierce, Catherine A.; Flannery, Alexander H.
Background: Preceptor development is a focus of pharmacy residency programs across the country. Graduation from residency into the role of preceptor can be a challenge, as it is one of many transitions junior practitioners make in their early careers. Literature in recent years has brought attention to the need to establish preceptor development programs that adequately allow newer preceptors to develop their skills in experiential education, for both pharmacy residents and students. Furthermore, many preceptor development programs as implemented are often didactic in nature, and include readings, webinars, and other passive learning regarding the art of precepting.Objective: Given the need to develop a preceptor development program in our service line that met the needs of preceptors-in-training and full preceptors, we offer a description of our preceptor development program in the intensive care unit.Methods: We focused on active development of preceptor skills for multiple layers of resident and student learners. In addition, this model incorporated instructing, modeling, coaching, and facilitating, as the relationship between full preceptor and preceptor-in-training evolved. It also offered the opportunity for real-time feedback and discussion on precepting performance.Conclusions: We describe our coprecepting model as an opportunity that succeeded for us in helping to transition our preceptors-in-training to full preceptors. It met the needs of our department, staff, and patients, and we believe it has the potential to be valuable as a tool extrapolated to the preceptor development programs of other institutions.